Lack of association between ENAM gene polymorphism and dental caries in primary and permanent teeth in Czech children - Borilova Linhartova, Petra; Deissova, Tereza; Musilová, Kristína; Zackova, Lenka; Kukletova, Martina; Kukla, Lubomir; Izakovicova Holla, Lydie (Clinical oral investigations, 2018)
OBJECTIVES: The enamelin gene (ENAM) polymorphism (rs12640848) was recently associated with dental caries in primary teeth in Polish children. The aims of the present study were to prove this association in primary dentition and to find a possible effect of this variant on caries development in permanent dentition in Czech children. MATERIALS AND METHODS: This study comprised 905 Czech children. Totally, 187 children aged 2-6 years with primary dentition [78 healthy subjects (with decayed/missing/filled teeth, dmft = 0) and 109 patients with early childhood caries (ECC; dmft ≥ 1)] were included in this case-control study. In addition, 177 subjects aged 13-15 years without caries (DMFT = 0) and 541 children with dental caries (DMFT ≥ 1) in permanent dentition were selected from the ELSPAC study. Genotype determination of the ENAM polymorphism (rs12640848) was based on the TaqMan method. RESULTS: No significant differences in the allele or genotype frequencies between the caries-free children and those affected by dental caries were observed in both primary and permanent dentitions. CONCLUSIONS: Lack of association between the ENAM polymorphism (rs12640848) and dental caries in Czech children was detected. CLINICAL RELEVANCE: Although ENAM is considered as a candidate gene for dental caries, the presence of the ENAM variant (rs12640848) cannot be used as a risk factor of this multifactorial disease in the Czech population.
Keywords: zuby mléčné; Dental Caries; Polymorphism, Single Nucleotide; Infant; Humans; extracelulární matrix - proteiny; kojenec; dítě; DMF Index; Child; dentice trvalá; jednonukleotidový polymorfismus; Female; Genotype; lidé; Tooth, Deciduous; Extracellular Matrix Proteins; předškolní dítě; zubní kaz; ženské pohlaví; Male; Adolescent; Dentition, Permanent; Czech Republic; genotyp; Česká republika; mužské pohlaví; Child, Preschool; mladiství